Seventeen Years' Experience of Peritoneal Dialysis in Iran: First Official Report of the Iranian Peritoneal Dialysis Registry. Issue 6 (September 2014) - Najafi, Iraj; Alatab, Sudabeh; Atabak, Shahnaz; Majelan, Nader Nouri; Sanadgol, Houshang; Makhdoomi, Khadijeh; Ardalan, Mohammad Reza; Azmandian, Jalal; Shojaee, Abbas; Keshvari, Amir; Hosseini, Mostafa
Background: To facilitate planning, national renal registries provide reliable and up-to-date information on numbers of patients with end-stage renal disease (ESRD), developing trends, treatment modalities, and outcomes. To that end, the present publication represents the first official report from Iranian Peritoneal Dialysis Registry. Methods: The prevalence, demographics, and clinical characteristics of patients on peritoneal dialysis (PD) were collected from all PD centers throughout the country. Results: By the end of 2009, the prevalence of ESRD was 507 per million population in Iran. The most common renal replacement modality was hemodialysis (51.2%), followed by kidney transplantation (44.7%), and then PD (4.1%). The mean age of PD patients was 46 years, and the most common causes of ESRD were diabetes (33.5%), hypertension (24.4%), and glomerulonephritis (8.2%). Overall patient mortality was 25%, with cardiac events (46%), cerebral stroke (10%), and infection (8%) being the main causes of death. The 1-, 3-, and 5-year survivals were 89%, 64%, and 49% respectively. The most common cause of dropout was peritonitis (17.6%). Staphylococcus (coagulase-negative and S. aureus ) was the most prevalent causative organism in peritonitis episodes; however, in more than 50% of episodes, a sterile culture was reported. Mean baseline serum hemoglobin and albumin were 10.7 g/dL and 3.6 g/dL respectively. Conclusions: Our registry results, representing the second largest report of PD in the Middle East, is almost comparable to available regional data. We hope that, in future, we can improve our shortcomings and lessen the gap with developed countries.